2000
DOI: 10.1002/1531-8249(200005)47:5<606::aid-ana8>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

The motor cortex shows adaptive functional changes to brain injury from multiple sclerosis

Abstract: Although multiple sclerosis (MS) is an inflammatory demyelinating disease, there can be substantial axonal injury and loss. We therefore hypothesized that adaptive cortical changes may contribute to limiting functional impairment, particularly in the early stages of the disease. To test our hypothesis, we used functional magnetic resonance imaging (MRI) to characterize the localization and volumes of activation in the motor cortex during simple flexion‐extension finger movements. There were differences in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
110
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(124 citation statements)
references
References 32 publications
12
110
2
Order By: Relevance
“…Aside from this influence of LL, cortical adaptive changes may also limit correlations between localized lesion probability and symptoms. Adaptive changes have been shown to contribute to functional recovery after axonal injury (32)(33)(34). These changes after axonal loss can involve local synaptic reorganization, reorganization at more distant sites, or recruitment of parallel existing pathways (33), hampering relations between the location of an original lesion and its remaining symptoms after the development of adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from this influence of LL, cortical adaptive changes may also limit correlations between localized lesion probability and symptoms. Adaptive changes have been shown to contribute to functional recovery after axonal injury (32)(33)(34). These changes after axonal loss can involve local synaptic reorganization, reorganization at more distant sites, or recruitment of parallel existing pathways (33), hampering relations between the location of an original lesion and its remaining symptoms after the development of adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that a part of explanation could be found in adaptation within the CNS. For example, recent brain imaging studies conducted on mildly involved MS patients have suggested normal neurological functioning due to cortical reorganization (Lee et al, 2000;Pantano et al, 2005;Reddy, Narayanan, Arnoutelis et al, 2000;. In addition, no performance deficits in reaction time motor tasks was observed between mildly affected MS patients (with a mean EDSS score of 1.4) indicating an adaptive mechanism in the cortex (Cerasa et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…8,[64][65][66] Thus, if RRMSPs showed restricted extent of activation compared to HCs, averaging across voxels in these ROIs might be expected to result in artificially attenuated BOLD-HRF peak amplitude. We tested for group differences in the percent of active voxels at each of the eight tent-derived time points (t 0 À t 7 ) in BA 4 and 17.…”
Section: Extent Of Spatial Activity Group Comparisonsmentioning
confidence: 99%